Profitability Analysis during the covid-19 and post-covid-19 periods at PT. KMI WIRE AND CABLE Tbk - fauziah, Putri; Anjani, Devi Nila; Safnah, Safnah; Fitri, Hafiza (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
The purpose of this study was to test company profitability during the covid-19 and post-covid-19 periods at PT KMI Wire and Cable Tbk. This data is obtained from the company's official website which is referenced from the Indonesian stock exchange page. The data was also confirmed through operational employees working at PT KMI Wire and Cable Tbk, for the 2019-2021 period. This type of research is descriptive and the data source used is secondary data. The research results show that the company's profitability experienced a shock during the Covid-19 pandemic, and after that difficult period, the company recovered and grew again. This is shown from the ratio of profitability to company performance in the period 2019 to 2021